2020
DOI: 10.2495/epm200051
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ground Thermal Control Systems for Solar Photovoltaic Performance Enhancement

Abstract: Arid areas are characterized by high solar radiation, which is an advantage for the performance of photovoltaic (PV) panels. However, they are deteriorating by two setbacks from the harsh climate: shallow temperatures during the night, leading to condensation and overheating during the day, leading to reduced efficiency. The paper discusses and resolves the two setbacks in the performance by cooling the panel during the day and heating it during the night using a ground embedded heat exchanger. Experimental an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An oscillatory heat exchanger configuration embedded in the ground is used by MN R et al to cool the panels during the day. As a result, the surface temperature of the PV during the day decreases by about 8°C, and the efficiency increases by 10% [22]. A similar study was conducted by Al-Waeli et al by choosing an oscillatory heat exchanger configuration to improve PV performance.…”
Section: Introductionmentioning
confidence: 79%
“…An oscillatory heat exchanger configuration embedded in the ground is used by MN R et al to cool the panels during the day. As a result, the surface temperature of the PV during the day decreases by about 8°C, and the efficiency increases by 10% [22]. A similar study was conducted by Al-Waeli et al by choosing an oscillatory heat exchanger configuration to improve PV performance.…”
Section: Introductionmentioning
confidence: 79%
“…They studied the water flow rate variation and found that it is insignificant, up to 0.024 kg/s. An innovative active cooling technology incorporating a ground heat exchanger with the PV panel has been developed by Reda et al [13,14]. They reported that the water ground heat exchanger reduced the temperature of the PV panel surface by around 8-10℃, which achieved 9.0% more efficiency than the non-cooled PV panel.…”
Section: Introductionmentioning
confidence: 99%
“…A new cooling approach using a backside water chamber was investigated experimentally and numerically as reported by Reda et al [26], Al-Kayiem and Reda [27], and Reda et al [28]. They circulated the cooling water through a ground heat exchanger.…”
Section: Introductionmentioning
confidence: 99%